Potential for import substitution of livestock products in the Republic of Kazakhstan - O. K. Denissova; M. V. Kozlova; M. U. Rakhimberdinova (Экономика: стратегия и практика)
The present paper aims to suggest possibilities of import substitution of livestock production in the Republic of Kazakhstan to increase the volume of own production.The methods used were empirical research methods (observation, description, comparison and generalization) and theoretical research methods (abstraction, analysis and synthesis, induction and deduction).The results of this research distinguish characteristics of the current livestock industry in Kazakhstan. The analysis of import was carried out and the main countries-importers of livestock products in the Republic of Kazakhstan were identified from the data of Customs statistics.The present recommendations could be useful as information and analytical guidance to follow trends for agroindustrial complex development and to create interregional and regional programs for livestock.Our work led us to conclude that Kazakhstan’s livestock industry has significant but not fully utilized potential for development. Own production of livestock in Kazakhstan is constrained by a number of the following factors: concentration of specific weight of cattle in personal subsidiary farms; a low share of breeding cattle in the general livestock population; a lack of infrastructure for livestock production; underdevelopment of processing production of agricultural products.A large part of basic food is imported to Kazakhstan. Import substitution should result to increase of the competitiveness of domestic products by stimulating technological modernization of production, increasing its efficiency and developing new competitive products.